Investigating emotional regulation, aggression and self-esteem in sexually abused adolescents - Uzun, Mehmet Erdem; Sezgin, Elif; Çakır, Zülfiye; Şirin, Hande (The European Research Journal, 2023)
Objectives: Child sexual abuse is a global problem with an increased risk of developing psychopathology. In recent studies, it was studied that children and adolescents who experienced sexual abuse have emotion regulation difficulties. We aimed to investigate some features of sexually abused adolescents by studying emotion regulation, aggression, and self-esteem. Methods: One hundred four adolescents seeking treatment after sexual abuse to Bursa Yuksek Ihtisas Training and Research Hospital Child Monitoring Center and 91 control group were included. Participants were given to complete the personal information form, the adolescent emotion regulation scale, the reactive-proactive aggression scale, and the Rosenberg self-esteem scale. Results: It was determined that adolescents who were sexually abused used more internal dysfunctional and external dysfunctional emotion regulation while the control group used more external functional emotion regulation. While there was no difference between both groups regarding aggression, self-esteem was found to be lower in abused adolescents. Self-injurious behavior was higher in adolescents victims of sexual abuse. Aggression was found to increase as dysfunctional emotion regulation increased. Conclusions: It was found that sexually abused adolescents had more difficulty in regulating their emotions and exhibited more self-injurious thoughts and behaviors but there was no difference between them and the control group in terms of aggression. We found that dysfunctional emotion regulation increased aggression in the study group.